YOUTH INNOVATION ACTIVISM IN SOCIETY SOCIO-PHILOSOPHICAL HARMONY WITH THE PRACTICE OF REFORM IN THE NEIGHBORHOOD - Abduvaliyev Ortiq Abdulhamidovich (International Scientific and Current Research Conferences, 2023)
It is an important process to focus the innovative activity of young people, accumulated at the expense of improving their knowledge, on solving social and economic problems in the regions, developing the lifestyle of the population, ultimately ensuring social stability. The article covers the same issue in detail. Youth Innovation activism is in harmony with the principles of the national interests of the country and the practice of reform, it has been said that improving the living well-being of the population, raising the lifestyle to a higher level, in this regard, programs compiled by the authorities and helping the ongoing efforts to become visible in practice.